Policies of improving developers’ willingness to implement prefabricated building: a case study from China - Su, Yikun; Xue, Hong; Han, Rui; Zhang, Shoujian; Sun, Zhi; Song, Yirou (Journal of Civil Engineering and Management, 2023)
Multiple policies have been formulated to promote the development of prefabricated building (PB). However, ineffective policies increase the financial burden of the governments and hinder PB development. This study aims to identify effective policies and develop a practical policy framework to encourage developers to implement PB. Text analysis is to identify the policies related to PBs from the numerous samples. A survey is to verify the effective policies and explore their effects on the developers’ willingness to implement PBs. The findings suggest that the current policy system of PBs is complete but uneven, focusing on environmental policies. The most cost-effective tools are land limitations, tax incentives, and financial support. Besides, policies are interrelated in affecting developers’ willingness to implement PBs. It provides a reference for policy evaluation in application scenarios, which expands the literature research on the policy. Meanwhile, it provides a guide for policymakers to evaluate the effectiveness of policies and formulate practical policy frameworks to promote PB development.